Astronomi eğitiminde Ay’ın evreleri ve tutulmalar konusu için geçerli ve güvenilir bir başarı testi geliştirme çalışması. - GÜNGÖR, Hülya; ÜNAL, İbrahim (Mehmet Akif Ersoy University Journal of Education Faculty, 2025)
In this study, an achievement test was developed for the subject of the phases of the Moon and eclipses in the astronomy course of the science teaching programme of universities. In order to develop an achievement test, firstly the purpose of the research was determined. Then, the subtopics of the phases of the Moon and eclipses in the science teacher education programme were formed. The questions of the test were prepared according to the sub-topics. The test, which initially consisted of 28 items, was reduced to 23 items due to content validity after expert opinion. For the pilot application, the achievement test was applied to 101 pre-service science teachers from the third and fourth grades who had received astronomy education in Malatya and Elazığ. After the application, item analyses of the test were performed with Microsoft Excel, SPSS and TAP programs. In data analysis, item difficulty and item discrimination indices were analysed. After the analysis, 3 more items were removed from the test and the achievement test was finalised with 20 questions. The KR-20 reliability coefficient of the test was calculated as 0.717. In addition, the average difficulty value of the test was 0.568 and the general discrimination index value was 0.44. From the data obtained, it was concluded that the test was highly reliable and discriminative. The Moon phases and eclipses achievement test can be used to determine the prior knowledge of the students, can be used within the scope of formative assessment activities during the teaching process, and can also be used after teaching.